Improving Teacher Discipline in Preparing Learning Tools Through Academic Supervision - Anismawati; Rambat Nur Sasongko; Connie (International Journal of Innovation and Education Research, 2023)
The purpose of this study was to describe efforts to improve teacher discipline in developing learning tools based on independent learning through academic supervision at Junior High School 01 Bengkulu Utara. The method used in this study is the act of supervision. Data collection techniques interview, observation and documentation. Data analysis uses average and percentage calculation techniques. Pre-cycle research showed that teachers laked discipline in preparing learning tools, so researchers carried out supervisory actions through academic supervision of class visit techniques, teacher meetings and direct approaches by school principals. The results showed that teacher discipline could increase by 80% or 8 teachers succeeded in developing learning tools based on independent learning at SMP Negeri 01 Bengkulu Utara.